High-strength and high-toughness ceramic composite material with wave occlusion structure and preparation method of high-strength and high-toughness ceramic composite material
By introducing an interlocking structure of wave occlusion structure into the silicon nitride ceramic material, the problem of insufficient mechanical performance of silicon nitride ceramics in extreme environments is solved, and the synergistic effect of high strength, high toughness and excellent wave transmissive performance is achieved.
Patent Information
- Application Number
- CN202411615027.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The existing silicon nitride ceramic materials lack mechanical properties in extreme environments, making it difficult to ensure the normal propagation of electromagnetic waves at high temperatures.
Using a high-strength and high-strength ceramic composite material with a wave-blocking structure, the interface layer is designed on the surface of the silicon nitride matrix and the interface layer are used to achieve mutual interlocking between the matrix and the interface layer, enhancing the material's resistance to local damage and energy absorption performance.
It achieves excellent wave transmission performance and high strength and toughness synergistic effects, improving the mechanical properties and impact resistance of the material in extreme environments.
Smart Images

Figure CN119462166A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of structural and functional integrated materials, and in particular relates to a high-strength and high-toughness ceramic composite material with a wave-interlocking structure and a preparation method thereof. Background Art
[0002] In today's world, ultra-high-speed aircraft, round-trip aircraft, space exploration aircraft and other aircraft are developing rapidly. The radome (window) and other parts are located at the nose of the aircraft cabin. They are not only the structural parts of the aircraft, but also an important part of the guidance system. They need to withstand the mechanical stress generated by the acceleration process of the aircraft and the thermal expansion caused by high temperature. As an important part of the transmission, they need to ensure the normal propagation of electromagnetic waves. There are great restrictions on the selection of high-temperature wave-transmitting materials.
[0003] Silicon nitride has become one of the preferred materials for high Mach number aircraft due to its excellent properties such as low dielectric constant, low dielectric loss, high bending strength and high thermal shock resistance. However, the intrinsic brittleness of silicon nitride ceramics limits its use in extreme environments. In order to further improve the mechanical properties of high-temperature wave-transmitting materials and ensure the normal propagation of electromagnetic waves in extreme environments, a new material needs to be developed. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a high-strength and high-toughness ceramic composite material with a wave-interlocking structure, which achieves the synergistic effect of excellent wave-transmitting performance and high strength and high toughness.
[0005] The invention also provides a method for preparing a high-strength and high-toughness ceramic composite material with a wave interlocking structure.
[0006] The first aspect of the present invention provides a high-strength and high-toughness ceramic composite material with a wavy interlocking structure, comprising a matrix and an interface layer arranged on the surface of the matrix, the matrix and the interface layer are interlocked with each other through an interlocking structure, the material of the matrix is silicon nitride, and the material of the interface layer is two phases of silicon nitride and boron nitride.
[0007] One of the technical solutions of the present invention regarding the high-strength and high-toughness ceramic composite material with a wave-interlocking structure has at least the following beneficial effects:
[0008] In nature, environmental pressures and predator-prey relationships drive arthropods to develop mechanically strong and multifunctional structures. Among them, the terrestrial insect "ironclad" family, especially the ironclad beetle, is famous among entomologists for its compression resistance and hardened forewings or hind wings that can be bent into steel mounting needles. This species increases the torsion resistance of the cone joint to more than 45 times its body weight by biting nuclei between cones. Bivalve marine shells show strength, stiffness and toughness that even exceed nacre. The superior mechanical properties of bivalve marine shells come from their cross-lamellar structure arranged in the shape of a "biting" man, also known as the wave bite structure. Alligators are highly adaptable living fossils with armor covering their backs. This skin shield is composed of bony plates, called osteoderms, interconnected by sutures and non-mineralized collagen fibers, providing dual functions of protection and flexibility. Composites with biological-like interlocking interfaces have been synthesized, which are almost several times stronger than composites that mimic nacre structures, while improving the fracture toughness of the material, as well as stiffness and biocompatibility.
[0009] On the one hand, the interface interlocking structure can be combined with other bionic materials to develop composite materials with better mechanical properties; on the other hand, the interface interlocking design principle can be used as an interface enhancement strategy for composite materials. The wave bite structure has strong resistance to local damage, and local failure will not lead to overall damage. When a crack appears on the surface of a unit, the adjacent units will limit its crack propagation, thereby inhibiting the overall damage of the structure. Therefore, compared with the integral structure, the interface interlocking structure has higher toughness and stability. Materials with interface interlocking structures can withstand higher energy absorption, because under impact loads, the load of interface interlocking structure materials is significantly reduced compared to integral materials, and they have better buffering capacity.
[0010] The high-strength and high-toughness ceramic composite material of the present invention comprises a matrix and an interface layer arranged on the surface of the matrix. The matrix and the interface layer are engaged with each other through an interlocking structure. The bionic structure in nature is borrowed to combine the bionic structure with silicon nitride composite ceramics to design a ceramic composite material with integrated structure and function, thereby achieving a synergistic effect of excellent wave transmission performance and high strength and high toughness.
[0011] According to some embodiments of the present invention, the shape of the interlocking structure comprises a wave shape.
[0012] The wavy interlocking structure has several beneficial effects. First, it can effectively disperse stress, enhance the material's ability to resist local damage, and prevent crack propagation. Second, the wavy design provides better mechanical engagement, improving overall toughness and stability. In addition, this structure can significantly reduce load transfer and improve buffering capacity when subjected to impact loads, thereby improving energy absorption performance. Overall, the wavy interlocking structure enables the material to achieve an excellent balance between strength and toughness.
[0013] According to some embodiments of the present invention, the high-strength and high-toughness ceramic composite material has a flexural strength of 380 to 600 MPa.
[0014] According to some embodiments of the present invention, the fracture toughness of the high-strength and high-toughness ceramic composite material is 6.8 to 13 MPa·m 1 / 2 .
[0015] The second aspect of the present invention provides a method for preparing the high-strength and high-toughness ceramic composite material of the first aspect of the present invention, comprising the following steps:
[0016] S1: dispersing silicon nitride powder in a first polymer solution to obtain a matrix slurry; dispersing silicon nitride powder and boron nitride powder in a second polymer solution to obtain an interface layer slurry;
[0017] S2: coaxially extruding the matrix slurry and the interface layer slurry into a coagulation bath, and obtaining a fiber monolith precursor after phase inversion;
[0018] S3: pressure-forming the fiber monolith precursor to obtain a ceramic green body, degreasing and sintering to obtain the high-strength and high-toughness ceramic composite material.
[0019] A technical solution in the method for preparing a high-strength and high-toughness ceramic composite material of the present invention has at least the following beneficial effects:
[0020] Through the preparation method of the present invention, the interface interlocking structure is introduced into the silicon nitride ceramic composite material, and a silicon nitride ceramic composite material with a wave bite structure is prepared, and the ceramic composite material has excellent bending strength and fracture toughness. The method uses the wave bite structure design principle as a composite material structure reinforcement strategy, and wraps a weak interface around the reinforcement phase through coaxial extrusion and phase transformation methods. During the sintering process, due to diffusion mechanisms such as flow mass transfer and liquid phase mass transfer, ceramic shrinkage and internal pores are eliminated, and the silicon nitride in the interface layer diffuses into the matrix, thereby forming an interlocking structure between the weak interface and the reinforcement phase matrix. The formation of the wave bite structure ensures the excellent wave transmission performance of the silicon nitride composite ceramic, while further improving the mechanical properties and impact resistance of the silicon nitride composite ceramic.
[0021] The preparation method of the present invention simplifies the process flow, and improves the consistency and uniformity of the material by coaxial extrusion and phase conversion. Secondly, the use of a polymer solution as a dispersion medium helps to better control the dispersion state of the powder, thereby improving the density of the composite material. In addition, the method can also reduce production costs, improve production efficiency, and promote the densification of the material during the sintering process, thereby improving the mechanical properties and durability of the final product. Finally, by introducing an interlocking interface structure, the energy absorption capacity of the material can be significantly improved, further enhancing its application potential. No expensive equipment and complex process control are required, the reaction conditions are not harsh, the raw materials are easily available, the production cost is low, and it is easy to industrialize production.
[0022] According to some embodiments of the present invention, the solute of the first polymer solution is polyethersulfone, and the solvent is N-methylpyrrolidone.
[0023] The first polymer solution is mixed with ceramic powder to form a slurry, and the slurry undergoes a phase transition with a coagulation bath (such as water). The NMP solvent in the slurry is extracted by the coagulation bath, and the remaining PES and ceramic powder in the slurry form a solid. This method is used to obtain a fiber precursor matrix.
[0024] According to some embodiments of the present invention, the concentration of the first polymer solution is 0.06 g / ml to 0.3 g / mL.
[0025] In step S1, the ratio of silicon nitride powder to the first polymer solution is: 20-90 g silicon nitride powder: 30-120 mL polymer solution.
[0026] According to some embodiments of the present invention, the solute of the second polymer solution is polyethersulfone, and the solvent is N-methylpyrrolidone.
[0027] The second polymer solution is mixed with the ceramic powder to form a slurry, and the slurry undergoes a phase transition with a coagulation bath (such as water). The NMP solvent in the slurry is extracted by the coagulation bath, and the remaining PES and ceramic powder in the slurry form a solid. This method is used to obtain a weak interface of the fiber precursor.
[0028] According to some embodiments of the present invention, the concentration of the second polymer solution is 0.06 g / ml to 0.3 g / mL.
[0029] In step S1, silicon nitride powder and boron nitride powder are dispersed in the second polymer solution, and the ratio of silicon nitride powder, boron nitride powder and the second polymer solution is: 1-12 g silicon nitride powder: 1-10 g boron nitride powder: 30-120 mL polymer solution.
[0030] According to some embodiments of the invention, the coagulation bath comprises deionized water.
[0031] Sintering aids such as Y 2 O 3 Powder and Al 2 O 3 pink.
[0032] Y 2 O 3 The powder acts as a sintering aid in the matrix, which can reduce the sintering temperature of silicon nitride composite ceramics and make the ceramics sintered more densely. Other sintering aids can be used to replace the ceramic powder.
[0033] Al 2 O 3 The powder also acts as a sintering aid in the matrix, which can reduce the sintering temperature of silicon nitride composite ceramics and make the ceramics sintered more densely. Other sintering aids can be used to replace the ceramic powder.
[0034] In step S2, the matrix slurry and the interface layer slurry are coaxially extruded into a coagulation bath, and the coagulation bath is water. When encountering water, the phase transition occurs. The "water-encountering" phase transition refers to the change from a solution film to a solid matrix when the polymer is exposed to water. When the polymer solution encounters water, the solvent in the solution is extracted by water, and the remaining polymer forms a solid phase matrix.
[0035] According to some embodiments of the present invention, the pressure of the pressure molding is 100-200 MPa, and a ceramic green body with a certain density is obtained after the pressure molding.
[0036] The pressure forming method can be: according to the size of the stainless steel mold, the coaxially extruded fiber monolithic precursor is cut, and then the cut fiber monolithic precursor is placed in the stainless steel mold for parallel arrangement, and then the mold is placed in a powder tablet press to pre-press to obtain a ceramic green body, and then the obtained ceramic green body is placed in a cold isostatic press, and a pressure of 100 to 200 MPa is applied to obtain a ceramic green body with a certain density.
[0037] Parallel arrangement is to lay the cut fiber precursors flat layer by layer at the same angle, mainly to obtain ceramic sheets with neat arrangement, which can be fired only one at a time.
[0038] According to some embodiments of the present invention, the pressure forming comprises pre-pressing, a first cold isostatic pressing, a second cold isostatic pressing and a third cold isostatic pressing performed in sequence.
[0039] According to some embodiments of the present invention, the pre-pressing pressure is 15-25 MPa.
[0040] According to some embodiments of the present invention, the holding time of the pre-pressing is 3 to 10 minutes.
[0041] According to some embodiments of the present invention, the pressure of the first cold isostatic pressing is 150-250 MPa.
[0042] According to some embodiments of the present invention, the holding time of the first cold isostatic pressing is 20 to 40 minutes.
[0043] According to some embodiments of the present invention, after the first cold isostatic pressing, a first heating and heat preservation is performed under a protective atmosphere to remove organic matter.
[0044] The purpose of the first cold isostatic pressing is to apply a higher pressure to make the sample that is initially formed into a block in the powder press more dense.
[0045] According to some embodiments of the present invention, the pressure of the second cold isostatic pressing is 150-250 MPa.
[0046] According to some embodiments of the present invention, the holding time of the second cold isostatic pressing is 20 to 40 minutes.
[0047] According to some embodiments of the present invention, after the second cold isostatic pressing, a second heating and heat preservation is performed in an air atmosphere to remove carbon.
[0048] Since the ceramic sheet undergoes a debinding process in an argon atmosphere in a tubular furnace, the polymers other than carbon are removed and the material has many pores, the sample needs to be densified by a second cold isostatic pressing process to prevent the sample from directly breaking after the second debinding and decarbonization.
[0049] According to some embodiments of the present invention, the pressure of the third cold isostatic pressing is 150-250 MPa.
[0050] According to some embodiments of the present invention, the holding time of the third cold isostatic pressing is 20 to 40 minutes.
[0051] The ceramic sheet is debinded in an air atmosphere in a tubular furnace. After the carbon is removed, the sample strength is low and there are more and larger pores inside. The purpose of the third cold isostatic pressing is to densify the sample.
[0052] According to some embodiments of the present invention, the degreasing process includes: heating the ceramic green body to 600-700° C. at a heating rate of 1-2° C. / min in an air atmosphere, and keeping the temperature for 2-6 hours to remove polyethersulfone in the ceramic green body.
[0053] According to some embodiments of the present invention, the sintering is pressureless sintering.
[0054] Pressureless sintering refers to the pressure being normal pressure, the purpose of which is to obtain dense silicon nitride composite ceramics. The reactions that occur include:
[0055] 1. α-Si 3 N 4 Transformed into β-Si 3 N 4 ;
[0056] 2. Grain growth;
[0057] 3. Material migration, grain boundary movement, pore elimination, shrinkage, and a dense block are obtained.
[0058] According to some embodiments of the present invention, the sintering is performed under a protective atmosphere.
[0059] According to some embodiments of the present invention, the sintering temperature is 1700-1800°C.
[0060] According to some embodiments of the present invention, the sintering holding time is 1 to 2 hours.
[0061] The purpose of sintering is to obtain dense silicon nitride composite ceramics. The reactions that occur are as follows:
[0062] (1) α-Si 3 N 4 Transformed into β-Si 3 N 4 ;
[0063] (2) Grain growth;
[0064] (3) Material migration, grain boundary movement, pore elimination, shrinkage, and a dense block are obtained.
[0065] The debinding process is in step three. The debinding process is divided into two steps. Polyethersulfone is removed in the two-step debinding process.
[0066] After sintering, a relatively dense, high-strength, high-toughness silicon nitride-based ceramic composite material with a wavy interlocking structure is obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 This is a cross-sectional microscopic morphology of the ceramic composite material prepared in Example 1.
[0068] Figure 2 This is a cross-sectional microscopic morphology of the ceramic composite material prepared in Example 2.
[0069] Figure 3 This is a cross-sectional microscopic morphology of the ceramic composite material prepared in Example 3.
[0070] Figure 4 This is a cross-sectional microscopic morphology of the ceramic composite material prepared in Example 4.
[0071] Figure 5 These are the X-ray powder diffraction test results of the ceramic composite materials prepared in Examples 1 to 4.
[0072] Figure 6 These are the test results of the flexural strength and fracture toughness of the ceramic composite materials prepared in Examples 1 to 4.
[0073] Figure 7 This is a microscopic morphology of the fracture toughness sample of the ceramic composite material prepared in Example 3. DETAILED DESCRIPTION
[0074] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0075] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0076] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0077] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0078] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0079] Example 1
[0080] A high-strength and high-toughness ceramic composite material with a wave-interlocking structure was prepared. In this embodiment, the volume ratio of the ceramic powder to the solution was 2 vol%. 3 N 4 The volume ratio of BN is 1:2.
[0081] The specific process is:
[0082] (1) Weighing Si 3 N4 Powder 81.00g, Y 2 O 3 Powder 5.40g, Al 2 O 3 3.60 g of SiO2 powder was mixed evenly with 100 mL of polyethersulfone (PES)-N-methylpyrrolidone solution (0.125 g / mL) to prepare the slurry for the matrix. 3 N 4 powder 1.29g, BN powder 1.83g, Al 2 O 3 Powder 0.139g, Y 2 O 3 0.208 g of powder was added, and the above four powders were mixed with 60 mL of polyethersulfone (PES)-N-methylpyrrolidone solution (0.1 g / mL) to form a slurry for preparing the interface. The above two slurries were put into a ball mill and ball milled at a speed of 300 rpm for 24 hours.
[0083] (2) The two slurries ball-milled in step (1) were poured into a 18-mesh small sieve for filtration, and then the slurries obtained after filtration were placed in a vacuum defoamer for defoaming at a speed of 500 rpm / min under vacuum for 30 min.
[0084] (3) The two slurries after degassing in step (2) are poured into different syringes, and the matrix slurry in the syringe is squeezed out into deionized water through the inner diameter (0.86 mm) needle port of the coaxial needle by a syringe pump, and the interface slurry is squeezed out into deionized water through the outer diameter (1.30 mm) needle port of the coaxial needle. A fiber precursor with interface coating is obtained by a phase inversion method, and the prepared fiber precursor is immersed in deionized water for 30 minutes to remove N-methylpyrrolidone, and finally the fiber precursor is placed in an oven for drying.
[0085] (4) Cut the fibers obtained in step (3), arrange them axially and stack them in a mold, and use a powder tablet press to cold-press the arranged fibers. The pre-pressing pressure is 20 MPa. After holding the pressure for 5 minutes, turn 90 degrees and apply pressure again. Repeat the operation three times to obtain a square block. The obtained block with a certain density is placed in a cold isostatic press, and a pressure of 200 MPa is applied and the pressure is maintained for 30 minutes to obtain a denser block. The block after the first cold isostatic pressing is placed in a tubular furnace, argon is introduced, and the temperature is raised to 650°C at a heating rate of 1 to 2°C / min. It is then kept at 650°C for 4 hours to remove organic matter, and then the block is densified again at a pressure of 200 MPa and a pressure of 30 minutes in the cold isostatic press. The block subjected to the second cold isostatic pressing is placed in a tubular furnace, air is introduced, and the temperature is raised to 650°C at a heating rate of 0.5-2°C / min. It is then kept at 650°C for 4 hours for decarbonization. The block after decarbonization is pressed in a cold isostatic press for the third time at a pressure of 200 MPa for 30 minutes.
[0086] The block in step (4) is placed in a vacuum sintering furnace and sintered at 1750° C. in a nitrogen atmosphere at normal pressure for 2 hours to obtain a high-strength and high-toughness silicon nitride composite ceramic with a wavy interlocking structure.
[0087] The cross section of the obtained silicon nitride composite ceramic was subjected to SEM analysis. Figure 1 As shown, the results show that this embodiment successfully prepares a silicon nitride ceramic composite ceramic with a wavy interlocking structure, and there is an interlocking structure between the fiber matrix and the cell body interface layer. The fiber matrix is mainly composed of silicon nitride, and the diameter of the fiber matrix is about 0.52 mm. The cell body interface layer is composed of silicon nitride and boron nitride, and the thickness of the cell body interface layer is about 16 μm.
[0088] It should be noted that the cross section of the silicon nitride ceramic composite ceramic is obtained by cutting the uneven cross section of the fracture toughness test sample with a diamond wire cutting machine. The height difference between the cells is eliminated, and a flat sample plane is obtained under a scanning electron microscope.
[0089] It should be noted that in step (1), Y 2 O 3 The powder acts as a sintering aid in the matrix and interface, reducing the sintering temperature of silicon nitride composite ceramics and making the ceramic sintering more dense. It can be omitted or other sintering aids can be used to replace the ceramic powder.
[0090] Al 2 O 3 It also acts as a sintering aid in the matrix and interface, reducing the sintering temperature of silicon nitride composite ceramics and making the ceramic sintering more dense. It can be omitted or other sintering aids can be used to replace the ceramic powder.
[0091] In step (4), the purpose of the first cold isostatic pressing is to apply a higher pressure so that the sample initially formed into a block in the powder tablet press becomes more dense.
[0092] Since the ceramic sheet undergoes a debinding process in an argon atmosphere in a tubular furnace, the polymers other than carbon are removed and the material has many pores, the sample needs to be densified by a second cold isostatic pressing process to prevent the sample from directly breaking after the second debinding and decarbonization.
[0093] The ceramic sheet is debinded in an air atmosphere in a tubular furnace. After the carbon is removed, the sample strength is low and there are more and larger pores inside. The purpose of the third cold isostatic pressing is to densify the sample.
[0094] In step (4), the purpose of pressureless sintering is to obtain a dense silicon nitride composite ceramic, and the reactions that occur include:
[0095] 1. α-Si 3 N 4 Transformed into β-Si 3 N 4 ;
[0096] 2. Grain growth;
[0097] 3. Material migration, grain boundary movement, pore elimination, shrinkage, and a dense block are obtained.
[0098] It should also be noted that the debinding process is in step (3), and the debinding process is divided into two steps. Polyethersulfone is removed in the two-step debinding process.
[0099] Example 2
[0100] A high-strength and high-toughness ceramic composite material with a wave-interlocking structure was prepared. In this embodiment, the volume ratio of the ceramic powder to the solution was 6.6 vol%. Si 3 N 4 The volume ratio of BN is 1:1.
[0101] The specific process is:
[0102] (1) Weighing Si 3 N 4 Powder 67.50g, Y 2 O 3 Powder 4.50g, Al 2 O 3 3.00 g of SiO2 powder was mixed evenly with 100 mL of polyethersulfone (PES)-N-methylpyrrolidone solution (0.125 g / mL) to prepare the slurry for the matrix. 3 N 4 powder 10.73g, BN powder 7.63g, Al2 O 3 Powder 0.82g, Y 2 O 3 1.22 g of powder was added, and the above four powders were mixed with 100 mL of polyethersulfone (PES)-N-methylpyrrolidone solution (0.1 g / mL) to form a slurry for preparing the interface. The above two slurries were put into a ball mill and ball milled at a speed of 300 rpm for 24 h.
[0103] (2) The two slurries ball-milled in step (1) were poured into a 18-mesh small sieve for filtration, and then placed in a vacuum defoamer for defoaming at a speed of 500 rpm / min under vacuum for 30 min.
[0104] (3) The two slurries after degassing in step (2) are poured into different syringes, and the matrix slurry in the syringe is squeezed out into deionized water through the inner diameter (0.86 mm) needle port of the coaxial needle by a syringe pump, and the interface slurry is squeezed out into deionized water through the outer diameter (1.30 mm) needle port of the coaxial needle. A fiber precursor with interface coating is obtained by a phase inversion method, and the prepared fiber precursor is immersed in deionized water for 30 minutes to remove N-methylpyrrolidone, and finally the fiber precursor is placed in an oven for drying.
[0105] (4) Cut the fibers obtained in step (3), arrange them axially and stack them in a mold, and use a powder tablet press to cold-press the arranged fibers. The pre-pressing pressure is 20 MPa. After holding the pressure for 5 minutes, turn 90 degrees and apply pressure again. Repeat the operation three times to obtain a square block. The obtained block with a certain density is placed in a cold isostatic press, and a pressure of 200 MPa is applied and the pressure is maintained for 30 minutes to obtain a denser block. The block after the first cold isostatic pressing is placed in a tubular furnace, argon is introduced, and the temperature is raised to 650°C at a heating rate of 1 to 2°C / min. It is then kept at 650°C for 4 hours to remove organic matter, and then the block is densified again at a pressure of 200 MPa and a pressure of 30 minutes in the cold isostatic press. The block subjected to the second cold isostatic pressing is placed in a tubular furnace, air is introduced, and the temperature is raised to 650°C at a heating rate of 0.5-2°C / min. It is then kept at 650°C for 4 hours for decarbonization. The block after decarbonization is pressed in a cold isostatic press for the third time at a pressure of 200 MPa for 30 minutes.
[0106] The block in step (4) is placed in a vacuum sintering furnace and sintered at 1750° C. in a nitrogen atmosphere at normal pressure for 2 hours to obtain a fiber monolithic structure silicon nitride composite ceramic with interlocking interfaces.
[0107] The cross section of the obtained silicon nitride composite ceramic was subjected to SEM analysis. Figure 2As shown, the results show that this embodiment also successfully prepared a high-strength and high-toughness silicon nitride ceramic composite ceramic with a wavy interlocking structure, with an interlocking structure between the fiber matrix and the cell body interface layer. The fiber matrix is composed of silicon nitride, the diameter of the fiber matrix is 0.44 mm, the cell body interface layer is composed of silicon nitride and boron nitride, and the thickness of the cell body interface layer is approximately 24 μm.
[0108] Example 3
[0109] A high-strength and high-toughness ceramic composite material with a wave-interlocking structure was prepared. In this embodiment, the volume ratio of the ceramic powder to the solution was 10 vol%. 3 N 4 The volume ratio of BN is 1:1.
[0110] The specific process is:
[0111] (1) Weighing Si 3 N 4 Powder 60.75g, Y 2 O 3 Powder 4.05g, Al 2 O 3 2.70 g of SiO2 powder was mixed evenly with 90 mL of polyethersulfone (PES)-N-methylpyrrolidone solution (0.125 g / mL) to prepare the matrix slurry. 3 N 4 powder 12.88g, BN powder 9.16g, Al 2 O 3 Powder 0.77g, Y 2 O 3 1.15 g of powder was added, and the above four powders were mixed with 80 mL of polyethersulfone (PES)-N-methylpyrrolidone solution (0.1 g / mL) to form a slurry for preparing the interface. The above two slurries were put into a ball mill and ball milled at a speed of 300 rpm for 24 h.
[0112] (2) The two slurries ball-milled in step (1) were poured into a 18-mesh small sieve for filtration, and then placed in a vacuum defoamer for defoaming at a speed of 500 rpm / min under vacuum for 30 min.
[0113] (3) The two slurries after degassing in step (2) are poured into different syringes, and the matrix slurry in the syringe is squeezed out into deionized water through the inner diameter (0.86 mm) needle port of the coaxial needle by a syringe pump, and the interface slurry is squeezed out into deionized water through the outer diameter (1.30 mm) needle port of the coaxial needle. A fiber precursor with interface coating is obtained by a phase inversion method, and the prepared fiber precursor is immersed in deionized water for 30 minutes to remove N-methylpyrrolidone, and finally the fiber precursor is placed in an oven for drying.
[0114] (4) Cut the fibers obtained in step (3), arrange them axially and stack them in a mold, and use a powder tablet press to cold-press the arranged fibers. The pre-pressing pressure is 20 MPa. After holding the pressure for 5 minutes, turn 90 degrees and apply pressure again. Repeat the operation three times to obtain a square block. The obtained block with a certain density is placed in a cold isostatic press, and a pressure of 200 MPa is applied and the pressure is maintained for 30 minutes to obtain a denser block. The block after the first cold isostatic pressing is placed in a tubular furnace, argon is introduced, and the temperature is raised to 650°C at a heating rate of 1 to 2°C / min. It is then kept at 650°C for 4 hours to remove organic matter, and then the block is densified again at a pressure of 200 MPa and a pressure of 30 minutes in the cold isostatic press. The block after the second cold isostatic pressing was placed in a tubular furnace, air was introduced, and the temperature was kept at 650°C for 4 hours for decarbonization. The block after decarbonization was pressed for the third time in a cold isostatic press at a pressure of 200 MPa for 30 minutes.
[0115] (5) The block in step (4) is placed in a vacuum sintering furnace and sintered at 1750° C. for 2 h in a nitrogen atmosphere to obtain a silicon nitride composite ceramic with interlocking interface.
[0116] The cross section of the obtained silicon nitride composite ceramic was subjected to SEM analysis. Figure 3 As shown, the results show that this embodiment successfully prepares a silicon nitride ceramic composite ceramic with an interface interlocking structure, an interlocking structure between the fiber matrix and the cell body interface layer, the fiber matrix is composed of silicon nitride, the diameter of the fiber matrix is about 0.61 mm, the cell body interface layer is composed of silicon nitride and boron nitride, and the thickness of the cell body interface layer is about 31 μm.
[0117] Example 4
[0118] A high-strength and high-toughness ceramic composite material with a wave-interlocking structure was prepared. In this embodiment, the volume ratio of the ceramic powder to the solution was 10 vol%. 3 N 4 The volume ratio of BN is 1:2.
[0119] The specific process is:
[0120] (1) Weighing Si 3 N4 Powder 81.0g, Y 2 O 3 Powder 5.40g, Al 2 O 3 3.60g of SiO2 powder was mixed evenly with 120mL of polyethersulfone (PES)-N-methylpyrrolidone solution (0.125g / mL) to prepare the slurry for the matrix. 3 N 4 powder 6.44g, BN powder 9.16g, Al 2 O 3 Powder 0.48g, Y 2 O 3 0.73 g of powder was added, and the above four powders were mixed with 60 mL of polyethersulfone (PES)-N-methylpyrrolidone solution (0.125 g / mL) to form a slurry for preparing the interface. The above two slurries were put into a ball mill and ball milled at a speed of 300 rpm for 24 hours.
[0121] (2) The two slurries ball-milled in step (1) were poured into a 18-mesh small sieve for filtration, and then the slurries obtained after filtration were placed in a vacuum defoamer for defoaming at a speed of 500 rpm / min under vacuum for 30 min.
[0122] (3) The two slurries after degassing in step (2) are poured into different syringes, and the matrix slurry in the syringe is squeezed out into deionized water through the inner diameter (0.86 mm) needle port of the coaxial needle by a syringe pump, and the interface slurry is squeezed out into deionized water through the outer diameter (1.30 mm) needle port of the coaxial needle. A fiber precursor with interface coating is obtained by a phase inversion method, and the prepared fiber precursor is immersed in deionized water for 30 minutes to remove N-methylpyrrolidone, and finally the fiber precursor is placed in an oven for drying.
[0123] (4) Cut the fiber precursor obtained in step (3), arrange it axially and stack it in a mold, and use a powder tablet press to cold-press the arranged fibers, with a pre-pressing pressure of 20 MPa. After holding the pressure for 5 minutes, turn 90 degrees and apply pressure again. Repeat the above three times to obtain a square block. The obtained block with a certain density is placed in a cold isostatic press, and a pressure of 200 MPa is applied and the pressure is maintained for 30 minutes to obtain a more dense block. The block after the first cold isostatic pressing is placed in a tubular furnace, argon is introduced, and the temperature is raised to 650°C at a heating rate of 1 to 2°C / min. After that, it is kept at 650°C for 4 hours to remove organic matter, and then the block is densified again at a pressure of 200 MPa and a pressure of 30 minutes in the cold isostatic press. The block subjected to the second cold isostatic pressing is placed in a tubular furnace, air is introduced, and the temperature is raised to 650°C at a heating rate of 0.5-2°C / min. It is then kept at 650°C for 4 hours for decarbonization. The block after decarbonization is pressed in a cold isostatic press for the third time at a pressure of 200 MPa for 30 minutes.
[0124] The block in step (4) is placed in a vacuum sintering furnace and sintered at 1750° C. in a nitrogen atmosphere for 2 hours at normal pressure to obtain a high-strength and high-toughness silicon nitride composite ceramic with a wavy interlocking structure.
[0125] The cross section of the obtained silicon nitride composite ceramic was subjected to SEM analysis. Figure 4 As shown, the results show that this embodiment successfully prepares high-strength and high-toughness silicon nitride ceramic composite ceramics with a wavy interlocking structure, the fiber matrix and the cell body interface layer are interlocked with each other, the fiber matrix is mainly composed of silicon nitride, the diameter of the fiber matrix is about 0.58mm, the cell body interface layer is composed of silicon nitride and boron nitride, and the thickness of the cell body interface layer is about 30μm.
[0126] In addition, it was found from the fracture mode that when the fracture was located at the weak interface, the crack deflected in both directions, and the load borne at the deflection to the fiber matrix was greater than the load at the unidirectional deflection. At the same time, this fracture mode can greatly increase the fracture work of the material.
[0127] Strength test
[0128] The bending strength of the material refers to the standard GB / T 6569-2006 “Test method for bending strength of fine ceramics” and is measured by the three-point bending method. The sample size is 4mm×3mm×36mm, the span during the test is 30mm, the test loading rate is 0.5mm / min, and the three-point bending test is carried out on a universal mechanical testing machine (C42.104, Xinsansi, China).
[0129] Fracture toughness test
[0130] The fracture toughness of the material was tested using the single-side cross-section beam method. The cross-section depth was 2 mm, the span was 30 mm, the sample size was 3 mm × 4 mm × 36 mm, and the test loading rate was 0.05 mm / min. The fracture toughness test was carried out on a universal mechanical testing machine (C42.104, Xinsansi, China).
[0131] Performance results test
[0132] Phase analysis
[0133] The fiber monolithic silicon nitride ceramic composite materials with interlocking interfaces prepared in Examples 1-4 were subjected to phase detection, and the test results are as follows: Figure 5 As shown, from Figure 5 It can be seen that within the test range of 10° to 70°, the phase composition of Examples 1, 3, and 4 is mainly β-Si 3 N 4 In Example 2, except for β-Si 3 N 4 In addition, the diffraction peaks of trace BN were also detected.
[0134] Mechanical properties test
[0135] The bending strength and fracture toughness of the ceramic materials prepared in Examples 1 to 4 are as follows: Figure 6 As shown, it can be seen that the ceramic materials prepared in Examples 1 to 4 have excellent mechanical properties. Specifically:
[0136] The material prepared in Example 1 has a bending strength of 583.3±44.56386MPa and a fracture toughness of up to 11.69016±1.48693MPa·m 1 / 2 .
[0137] The material prepared in Example 2 has a bending strength of 447.78±37.72757MPa and a fracture toughness of 8.0323±1.26108MPa·m 1 / 2 .
[0138] The material prepared in Example 3 has a bending strength of 576.99±30.0009MPa and a fracture toughness of 6.83003±0.84111MPa·m 1 / 2 .
[0139] The material prepared in Example 4 has a bending strength of 387.80333±53.97114MPa and a fracture toughness of 12.91133±1.79621MPa·m 1 / 2 .
[0140] Fracture mode
[0141] Example 3 has excellent mechanical properties. The fracture behavior of the fracture toughness sample of Example 3 was observed. Figure 7 As shown, it presents a step shape, not a brittle fracture. When observing the fracture, it is found that when the cross section is exactly at the weak interface, it means that the sample can withstand a larger load. The mechanism of action is: after the load is applied, because a larger load is required for the crack at the cross section to extend toward the matrix, the crack at the cross section preferentially extends inward along the weak interface, and then the crack deflects inward and finally reaches the matrix. In order to further expand, the crack finally needs to occur at the cross section and within the cross section at the same time.
[0142] Interlocking structure introduction mechanism
[0143] Before the fiber monolithic composite material is sintered, since the polyethersulfone in the matrix and interface layer is removed during the debinding process, there are a lot of pores inside the fiber monolithic composite material. During the sintering process, hexagonal boron nitride is difficult to densify due to its special lamellar structure and low self-diffusion coefficient, so it exists in the interface. Due to the diffusion mechanism of flow mass transfer and liquid phase diffusion, the bonding and rearrangement between silicon nitride particles and the sintering aid Y 2 O 3 and Al 2 O 3 As the liquid phase diffuses, the pores are gradually filled, shrunk and deformed, and eventually transformed into isolated closed pores. The grain boundaries begin to move, and the pores gradually migrate to the grain boundaries and finally disappear. At the same time, due to the diffusion of silicon nitride in the interface into the matrix, the grain boundaries have different diffusion rates of silicon nitride in the interface layer, and the interface layer and the matrix intersect with each other, eventually forming an interfacial interlocking structure.
[0144] A major problem with silicon nitride ceramics as structural materials is their brittleness. Although many methods have been tried to improve their toughness, including the addition of fiber, whisker or particle reinforcement, ZrO 2 phase change enhancement, etc., but so far, the brittleness of ceramics has not been overcome in nature.
[0145] The present invention realizes the introduction of an interlocking structure of an interface into a silicon nitride ceramic composite material, and prepares a silicon nitride ceramic composite material with a wave bite structure, and the ceramic composite material has excellent bending strength and fracture toughness. The present invention provides a method for preparing a high-strength and high-toughness silicon nitride composite ceramic with a wave bite structure. The invention successfully introduces a weak interface whose main component is boron nitride into a silicon nitride matrix by a coaxial extrusion and phase transformation method, and realizes the interlocking of the interface between the weak interface and the matrix phase by diffusion and mass transfer during the ceramic sintering process. By forming an interlocking structure between the weak interface and the reinforcing phase matrix, while ensuring the excellent wave transmission performance of the silicon nitride composite ceramic, the mechanical properties and impact resistance of the silicon nitride composite ceramic are further improved. The reinforcing phases of the silicon nitride composite ceramics prepared in Examples 1 to 4 are wrapped by weak interfaces and interact with each other. When the material breaks, when the crack expands to the weak interface, the crack deviates, the crack expansion path increases, and the crack tension decreases, thereby increasing the mechanical properties and impact resistance of the material. The fracture toughness of Example 4 is as high as 12.91133±1.79621MPa·m 1 / 2 .
[0146] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A high-strength and high-toughness ceramic composite material with a wave-interlocking structure, characterized in that: The invention comprises a substrate and an interface layer arranged on the surface of the substrate, wherein the substrate and the interface layer are engaged with each other through an interlocking structure, the substrate is made of silicon nitride, and the interface layer is made of two phases of silicon nitride and boron nitride.
2. The high-strength and high-toughness ceramic composite material according to claim 1, characterized in that: The shape of the interlocking structure includes a wave shape.
3. The high-strength and high-toughness ceramic composite material according to claim 1 or 2, characterized in that: The high-strength and high-toughness ceramic composite material has a flexural strength of 380 to 600 MPa; and / or the high-strength and high-toughness ceramic composite material has a fracture toughness of 6.8 to 13 MPa·m 1 / 2 .
4. A method for preparing a high-strength and high-toughness ceramic composite material as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1: dispersing silicon nitride powder in a first polymer solution to obtain a matrix slurry; dispersing silicon nitride powder and boron nitride powder in a second polymer solution to obtain an interface layer slurry; S2: coaxially extruding the matrix slurry and the interface layer slurry into a coagulation bath, and obtaining a fiber monolith precursor after phase inversion; S3: pressure-forming the fiber monolith precursor to obtain a ceramic green body, degreasing and sintering to obtain the high-strength and high-toughness ceramic composite material.
5. The preparation method according to claim 4, characterized in that: The solute of the first polymer solution is polyethersulfone, and the solvent is N-methylpyrrolidone; and / or, the concentration of the first polymer solution is 0.06g / ml to 0.3g / mL; and / or, the solute of the second polymer solution is polyethersulfone, and the solvent is N-methylpyrrolidone; and / or, the concentration of the second polymer solution is 0.06g / ml to 0.3g / mL.
6. The preparation method according to claim 4, characterized in that: The coagulation bath includes deionized water.
7. The preparation method according to claim 4, characterized in that: The pressure forming comprises pre-pressing, first cold isostatic pressing, second cold isostatic pressing and third cold isostatic pressing which are performed in sequence.
8. The preparation method according to claim 7, characterized in that: The pre-pressing pressure is 15-25 MPa; and / or, the holding time of the pre-pressing is 3-10 min; and / or, the pressure of the first cold isostatic pressing is 150-250 MPa; and / or, the holding time of the first cold isostatic pressing is 20-40 min; and / or, after the first cold isostatic pressing, a first heating and heat preservation is carried out in a protective atmosphere to remove organic matter; and / or, the pressure of the second cold isostatic pressing is 150-250 MPa; and / or, the holding time of the second cold isostatic pressing is 20-40 min; and / or, after the second cold isostatic pressing, a second heating and heat preservation is carried out in an air atmosphere to remove carbon; and / or, the pressure of the third cold isostatic pressing is 150-250 MPa; and / or, the holding time of the third cold isostatic pressing is 20-40 min.
9. The preparation method according to claim 4, characterized in that: The degreasing process comprises: heating the ceramic green body to 600-700° C. at a heating rate of 1-2° C. / min under air atmosphere, keeping the temperature for 2-6 hours, and removing polyethersulfone in the ceramic green body.
10. The preparation method according to claim 4, characterized in that: The sintering is carried out under a protective atmosphere; and / or the sintering temperature is 1700-1800° C.; and / or the sintering holding time is 1-2 hours.
Citation Information
Patent Citations
Process for preparing weak interface fiber monolith hafnium boride ceramic by wet spinning and co-extrusion method
CN111848175A
Preparation of fiber monolith zirconium boride ceramic with SiCw as interface through wet spinning and co-extrusion
CN111875406A
Nitride ceramic-based wave-transparent composite material and preparation method thereof
CN114804891A
Nitride fiber reinforced silicon nitride composite material and preparation method and application thereof
CN117466659A
Preparation of silicon nitride-based composite material with superhigh tenacity
CN1232805A